Making the UGM dormitory student returning procedure during the COVID-19 pandemic - Humaidy, Raudia Faridah; Bintoro, Bagas Suryo; Azizatunnisa’, Luthfi (BKM Public Health and Community Medicine, 2021)
Objective: Along with the decline in COVID-19 cases in Indonesia, UGM implements Controlled Face-to-face Learning (PTM). Various efforts have been made to prepare campus systems and infrastructure, one of which is dormitories as accommodation for students. Dormitories need to have a procedure for returning students to their dormitories to control COVID-19. This is a mentoring activity carried out by students of the Master's in Public Health to develop the procedure within the UGM Health Promoting University framework. Contents: The health protocol implementation procedure begins with identifying data needs in the field online and offline through hostel managers and administrators, dormitory residents, and the UGM COVID-19 Task Force. In this process, current health protocols are available but are not sufficient for repopulation conditions. These results are then followed up with the preparation of a draft procedure. In addition, mentoring activities also develop educational media that support the implementation of health protocols in dormitories. The draft procedure and educational media were then discussed together by the team with the dormitory manager. The procedure is integrated into the existing system and adapted to the system and resource availability. Future residents of the dormitory need to pay attention to several things, such as (1) confirming the arrival date and preparing a parental consent letter, (2) screening at the GMC, and (3) conducting a 14-day quarantine. The challenge in this activity is the online coordination process with hostel managers and administrators, dorm residents, and the UGM COVID-19 Task Force. This procedure requires adaptation and cooperation between the manager and the occupants. Dormitory managers need to monitor and evaluate the implementation of these procedures. This procedure is also expected to be an example to be applied elsewhere.